Expression Of Presupposition In Artistic Texts - Pulatova Dildora Dilmuradovna (Genius Journals, 2025)
In the article, the presuppositional features of the forms of reference in the Uzbek language are analyzed on the basis of the linguopragmatic approach on the example of literary texts. The function of address units in the speech situation and their role in expressing the relationship between the addresser and the addressee are highlighted. Also, transmission of hidden (presuppositional) information about the characters' social status, age, gender, and psychological state is revealed through the forms of reference.
Keywords: presupposition; forms of reference; linguo-pragmatics